(untitled) (New York, 2002)
Includes two part: Part 1 introduces the reader to the concept of "permeable insulation" and provides a detailed review of past practices and changes in policy. Part 2 deals with international trade issues, Japan's compliance with and resistance to global trade rules, and the domestic interests visible in Japan's compliance. Part 3 focuses on domestic measures and policies that Japanese firms have used to adapt to the changes, within Japan and abroad, triggered by globalization and liberalization
Keywords: Nhật Bản,Japan,Toàn cầu hóa,Globalization; Điều kiện kinh tế,Economic conditions,Khía cạnh kinh tế,Economic aspects; 1989-,1989-; Nhật Bản,Japan